Guguru ka Urug: The Existence of the Karuhun Tradition in the Kasepuhan Community of Urug Village in Supporting Sustainable Agriculture - Purwandari, Heru; Hasantie, Annisa Nurul; Fadili, Muhamad; Nugraha, Agung; Fisyhuri, Yuswikha Astafirdha; Novianti, Vina; Sulistiawati, Asri; Kartika, Juang Gema (Wacana Journal of Social and Humanity Studies, 2026)
The Karuhun tradition in Urug Village is a form of agricultural management based on local wisdom that is environmentally friendly and sustainable, despite being situated within a modern farming system that has negative environmental impacts. This research aims to identify the characteristics of the Karuhun tradition in supporting sustainable agriculture, analyze the influence of applying the Karuhun tradition on sustainable agriculture, and formulate recommendations for policy strategies. A mixed-methods approach was employed, utilizing snowball sampling with four informants and purposive sampling with 30 respondents. Data analysis used narrative analysis, multiple linear regression, stakeholder analysis, and TOWS Matrix. The results of the research showed that the characteristics of the Karuhun tradition consisted of talek, the principle of ngaji diri, and agricultural cultivation practices. The variables of Talek and agricultural cultivation practices have a positive impact on the success of implementing sustainable agriculture. The most important stakeholder is the Head of the Urug Village Customary Council. Recommendations for policy strategies include the development of edutourism, preserving traditions in the younger generation, collaboration among stakeholders, and strengthening the capacity of human resources in the use of agricultural technology. Keywords: Ancestral Traditions, Local Wisdom, Sustainable Agriculture, Talek